¡PONGAN DE CABEZA A ESE SANTO! - Bouroncle Caro, Antonio (1997)
It is a case study on the creation, growth and transformation of a medical center into a clinic. Its trajectory follows the rhythm of the country's economic situation, it opens new services when demand increases, which it finances with contributions from new partners and then with loans. When you go through an economic situation that can turn into insolvency, not all partners agree on the causes. Likewise, important changes in the market, such as the creation of new health service organizations and the entry of other competitors, generate solution proposals. Among others, the adoption of a total quality system is accepted. Ten months after its implementation, the situation does not improve and opinions on the effects of the program are divided. An advisor points out that the clinic's problem is financial. The case describes problems in the operation of the clinic and includes an annex section containing the financial statements for the last three years and information on bed occupancy.